Sucrose Accumulation Maturity Curves for CP 88-1762 - Robert A. Gilbert; James M. Shine, Jr.; Jimmy D. Miller; Ronald W. Rice; Curtis R. Rainbolt (EDIS)
This fact sheet presents the sucrose accumulation maturity curves for different crop ages (plant cane, 1st ratoon, and 2nd ratoon) of CP 88-1762. CP 88-1762 harvest samples were collected at 2-week intervals at 5 locations over 4 harvest seasons in the Everglades Agricultural Area. Biomass and sugar yields were determined on all samples in order to generate SPT trends over time. A full comparison of CP 88-1762 SPT trends with 12 other CP cultivars may be found in EDIS publication SS-AGR-221 Maturity Curves and Harvest Schedule Recommendations for CP Sugarcane Varieties (http://edis.ifas.ufl.edu/SC069). This document is SS-AGR-219, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published April 2004. Reviewed March 2005.